Careers in focus. Energy. - Ferguson Publishing (New York : Ferguson's, 2012)
Provides information on careers in the energy industry, including average salary and vocational outlook.
Bioenergy/biofuels workers -- Coal miners -- Energy conservation technicians -- Energy transmission and distribution workers -- Geologists -- Geophysicists -- Line installers and cable splicers -- Mining engineers -- Nuclear engineers -- Nuclear reactor operators and technicians -- Occupational safety and health workers -- Petroleum engineers -- Petroleum technicians -- Petrologists -- Power plant workers -- Radiation protection technicians -- Renewable energy careers -- Roustabouts -- Solar engineers --Surveyors.
Includes bibliographical references and index.
Keywords: Energy industries -- Vocational guidance -- Juvenile literature; Energy industries -- Vocational guidance; Vocational guidance